Age at first birth and long-term mortality for mothers: the Ohsaki cohort study - Taichi Sakai; Yumi Sugawara; Ikue Watanabe; Takashi Watanabe; Yasutake Tomata; Naoki Nakaya; Ichiro Tsuji (Komiyama Printing Co. Ltd, 2017)
Abstract Background Although maternal age at first birth has been rising in many developed countries, its long-term effects on the health of the mothers themselves are unclear. In this study, we investigated the relationship between maternal age at first birth and long-term mortality. Methods We conducted a cohort study of 20,624 parous Japanese women aged between 40 and 79 years in 1994 and followed up their survival for 14 years. Based on maternal age at first birth, the women were divided into four groups: ≤19 years, 20-24 years, 25-29 years, and ≥30 years. Using the 20-24 years group as a reference, hazards ratios (HRs) for all-cause and cause-specific mortality were calculated. Results Multivariate HRs for all-cause mortality were 1.17 in the ≤19 years group, 1.09 in the 25-29 years group, and 1.33 in the ≥30 years group. A U-shaped relationship was apparent between maternal age at first birth and mortality. This relationship was also observed for mortality attributable to cancer, cardiovascular disease and other diseases. This U-shaped relationship was observed only for women born before 1935 and the birth year of the first child before 1960. Conclusion A U-shaped relationship was apparent between maternal age at first birth and mortality. As maternal age at first birth is rising worldwide, the risk it imposes appears to have significance in the context of public health.